Differential Evolutionary History in Visual and Olfactory Floral Cues of the Bee-Pollinated Genus Campanula (Campanulaceae) - Paulo Milet-Pinheiro; Pablo Sandro Carvalho Santos; Samuel Prieto-Benítez; Manfred Ayasse; Stefan Dötterl (Plants, 2021)
Visual and olfactory floral signals play key roles in plant-pollinator interactions. In recent decades, studies investigating the evolution of either of these signals have increased considerably. However, there are large gaps in our understanding of whether or not these two cue modalities evolve in a concerted manner. Here, we characterized the visual (i.e., color) and olfactory (scent) floral cues in bee-pollinated Campanula species by spectrophotometric and chemical methods, respectively, with the aim of tracing their evolutionary paths. We found a species-specific pattern in color reflectance and scent chemistry. Multivariate phylogenetic statistics revealed no influence of phylogeny on floral color and scent bouquet. However, univariate phylogenetic statistics revealed a phylogenetic signal in some of the constituents of the scent bouquet. Our results suggest unequal evolutionary pathways of visual and olfactory floral cues in the genus Campanula. While the lack of phylogenetic signal on both color and scent bouquet points to external agents (e.g., pollinators, herbivores) as evolutionary drivers, the presence of phylogenetic signal in at least some floral scent constituents point to an influence of phylogeny on trait evolution. We discuss why external agents and phylogeny differently shape the evolutionary paths in floral color and scent of closely related angiosperms.